YOUTH IN EMILY DICKINSON'S POEMS (2003): SEMIOTIC CRITICISM - JUNIARDI, MIAMARTHA AYU (2011)
The major problem of this study is how youth is dscribe based on the structural elements in part one life. The objective of this study is to analyze the poem based on its structural elements in part one life, and based on semiotic criticism. The benefits of the study are to give in the application of semiotic criticism in literary study. The study belongs to the qualitative study. The object of the study is Youth in Emily Dickinson's Poems published by Martha Dickinson Bianchi and copyright 2003 by Jim Manis as the faculty editor of Pennsylvania state university. The primary data source is the main data obtained from all Emily Dickinson's poems related to the topic and the secondary data sources are the other data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by note-taking for the texts. The technique of data analysis used in this study is descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, it is apparent that in this poems Emily Dickinson is the great man of letters. The structural elements are coherent each other Second, based on the semiotic analysis, it shows that the poems being the beautiful unity, interdependent poems, and related to each other. Third, based on the youth analysis, Emily wanted to show the drawing of youth in her poem are on the psychological mental and emotional aspect.